Asian perspectives on international investment law - Nakagawa, Junji 1955- (Routledge research in internationl economic law, 2019)
With changes to the international investment law landscape and Asian countries now actively developing their network of bilateral investment treaties (BITs) and free trade agreements (FTAs), this volume studies issues relating to Asian perspectives on international investment law and forecasts the future of Asian contribution to its science and practice. The book discusses the major factors that have been driving Asian countries to new directions in international investment rule-making and dispute settlement. It also looks at whether Asian countries are crafting a new model of international investment law to reflect their specific socio-cultural values. Finally, the book examines whether there are any 'Asian' styles of international investment rule-making and dispute settlement, or if individual Asian countries are seeking specific national 'models' based on economic structure and geopolitical interests. This unique collection is exceptionally useful to students, scholars and practitioners of international investment law, international trade law and public international law